Efficient ecological restoration method for slope in South China - QIN XIAOFENG; JIANG YANBO; LI CAIXIA; XU CHUANYUN; WU GANGGANG; CHEN QIANFENG; SU XIANGHUA (2017)
The invention discloses an efficient ecological restoration method for a slope in South China. The efficient ecological restoration method comprises the following steps that the bare slope face is cleaned, a net is fixed to the slope face, and a planting matrix or covering soil is sprayed; thysanolaena maxima spikelets and caryopsises are selected; then white tephrosia seeds are selected and processed; bacteria-removed sawdust is soaked in water, thereby fully absorbing water, then the bacteria-removed sawdust is dredged out, the bacteria-removed sawdust, the thysanolaena maxima spikelets and caryopsises and bermuda grass seeds are mixed evenly, and standing is conducted; and the bacteria-removed sawdust and the bermuda grass seeds mixed with the thysanolaena maxima spikelets and caryopsises, the white tephrosia seeds, fertilizer and water are evenly mixed and stirred to be made into spray-seeding materials, the spray-seeding materials are sprayed through a spray-seeding machine or are sown manually onto mud